Design and performance of a laminar shear container for shaking table tests. Issue 135 (August 2020) - Li, Yadong; Zheng, Sen; Luo, Weili; Cui, Jie; Chen, Qianran
Abstract: In shaking table tests, appropriate boundary conditions are required in order to simulate semi-infinite seismic soil deposit responses within a finite size soil container. In this study, a laminar shear container with variable stiffness, constructed with a stack of steel hollow frames supported by ball bearings and bolts, was designed. The stiffness of the container can be changed by adjusting the number of frame, and row of bolts, and the connection form of bolts. Ten cases of shaking table tests were performed in order to determine the fundamental frequency of the sand deposit and to investigate boundary effects of the container. Results showed that the newly constructed laminar container has little boundary effects on the soil and is able to maintain the in-plane free-field response. Highlights: A new laminar shear container with changeable stiffness is designed for shaking table tests. The performance of the container is evaluated by a numerical study and a series of shaking table tests. The fundamental frequency of the container ranges from 2.37 Hz to 8.57 Hz. The boundary effects of the container are found to be negligible.